Composition optimization and characterizations of poly(L-lactic acid)/cellulose acetate blends films in solvent mixture system - Witthayaprapakorn, Chinanat; Thananukul, Kamonchanok; Suttenun, Nuchada; Punyamoonwongsa, Patchara; Molloy, Robert (Progress in Applied Science and Technology, 2015)
A biomaterial was developed by blending a commercially available poly(L-lactic acid) (PLLA) with cellulose acetate (CA) using a solvent casting technique. PLLA and CA have great potential for the manufacture of environmentally friendly thin films packaging but there is very limited number of studies on their blend compatibility. This work aimed to evaluate the compatibility of PLLA and CA in a solution form. The solution blends of various PLLA/CA weight percentages (0-100 %w/w) were prepared in a chloroform/acetone mixture solvent. Both physical and spectroscopic techniques were employed to characterize the homogeneity, structural integrity and various physicochemical properties of the films. Results indicated that PLLA was partially compatible with CA and the optically transparent films were only observed in either the PLLA- or CA-rich blend. However, this limit could be further extended by partial hydrolysis of the two polymers through the addition of hydrochloric acid. By altering some experimental conditions, a wide range of PLLA/CA films with different properties were fabricated. Interestingly, the Scanning Electron Microscopy (SEM) micrographs of the acid-free 40/60 blend film revealed the spherical agglomerated PLLA particles throughout the CA domain. Such embedded particles reinforced the thin film, as confirmed by the increased tensile strength comparing to that of the neat PLLA and CA films. This suggested the possible intermolecular interactions between the two components. The PLLA/CA blend system thus demonstrated its potential use for a wide range of applications, particularly in the manufacture of novel active biodegradable packing.